Age-Dependent Skeletal Muscle Response to Mechanical Injury Under Halothane Anesthesia in Rats: A Histological and Immunohistochemical Study - Fayzillayevich, Umurov B.; Ugli, Tilavov T.B.; Akhrorovna, Khasanova D. (Ibnosina Journal of Medicine and Biomedical Sciences, 2025)
Skeletal muscle regeneration following traumatic injury is influenced by age, anesthetic exposure, and systemic inflammatory responses. We aimed to evaluate the morphological changes in skeletal muscle tissue after mechanical injury under halothane inhalation anesthesia in rats of different ages.A total of 120 male Wistar rats aged 3, 6, and 12 months were subjected to closed soft tissue injury in the right hindlimb. Following trauma, all animals received halothane (10 ppm) as general inhalation anesthesia. Muscle biopsies were collected at 24, 72, and 168 hours postinjury. Histological, histochemical, and immunohistochemical assessments were conducted to evaluate muscle fiber edema, inflammatory infiltration, degenerative changes, and tissue regeneration.Age significantly influenced the severity and progression of morphological changes. Younger rats (3 months) exhibited faster recovery, with reduced inflammation and earlier onset of regeneration. Older rats (12 months) showed delayed and prolonged inflammation, more severe degeneration, and slower regenerative activity. The 6-month-old group demonstrated intermediate responses.Halothane anesthesia, combined with mechanical trauma, reveals age-dependent differences in skeletal muscle recovery. Younger animals exhibit more efficient regenerative responses, highlighting the impact of age on postinjury healing and inflammatory modulation in skeletal muscle tissue.
Keywords: age-related response; experimental trauma; halothane anesthesia; immunohistochemistry; morphological changes; skeletal muscle injury; Wistar rats